(untitled) (Journal of the College of Basic Education, 2022)
This research is concerned with studying the design diversity of the word majesty in the Configuring of Arabic calligraphy, as Arabic calligraphy is considered one of the most important arts in which Muslim calligraphers have excelled. Because this art is linked to the sanctity of the Holy Qur’an, as this calligraphy has developed and its forms and varieties have multiplied with the flourishing of Islamic civilization, and the word Majesty (God) has received the attention and care of calligraphers from the beginning of Islam to the present day, which gave it a Premium privacy in its positioning in the middle or above the calligraphy configuration and its non-duality or repetition of monotheism. and the researcher defined the problem of his research by the following question: What is the diversity in the diversity of the word majesty in Arabic calligraphy Configuring? Therefore, the research meant to identify the design diversity of the word Majesty (God) in Arabic calligraphy Configuring, for the period from (1383 AH - 1972 AD) to (1440 AH - 2018 AD),in Iraq and Turkey, the second chapter included the theoretical framework, where the first topic dealt with the design diversity of the word “majesty” (God), and the second topic included the calligraphy Configuring of the word “majesty” (God), then followed by the indications of the theoretical framework, and previous studies, and the third chapter included procedures The research, as the researcher adopted the descriptive approach (content analysis), and the fourth chapter included analyzing samples, presenting results and conclusions, recommendations and proposals.